The Effect of Digital Economy and Artificial Intelligence on The Participants of The School Educational Process - Vinichenko, Mikhail V. (2020)
The article examines the nature of the effect of the digital economy and artificial intelligence on the participants of the school educational process. The study deploys a Likert scale questionnaire, focused interview, and IBM SPSS Statistics 22 as the main instruments. The authors determine the status of a teacher in the AI-teacher system and identify the nature of AI’s influence on the students and communication within the teacher-student-teacher system. Support is provided for the hypothesis suggesting that the effect of the digital economy and AI on the participants of the school educational process (teachers and students) is complex and controversial and causes the differences in the teachers’ positions depending on their age, working experience, and the subject of specialization. The primary advantage of the article is the identification of stable relationships in the teacher-student-teacher system developing with the help of AI. The study indicates the teacher’s advantage over AI in teaching technique and social influence, as well as the negative effect of AI on students’ health. For the first time, the authors examine the nature of role changes in the AI-teacher system in the context of a global pandemic. The danger of AI replacing teachers with the help of teachers themselves is identified. The acquired results may be used by theorists and practitioners for further development of the foundations of the system of education and human interaction with AI in the digital economy.